2022
DOI: 10.1039/d1nr08101b
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, pathology and the biomolecular corona: the confounding factors in nanomedicine design

Abstract: The biomolecular corona that forms on nanomedicines in different physiological and pathological environments confers a new biological identity. How the recipient biological system's state can potentially affect nanomedicine corona formation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 220 publications
0
9
0
Order By: Relevance
“…[19][20][21][22][23] Consequently, understanding formation of the protein corona on NPs and characterizing its composition are major challenges for suc-cessful development of nanomedicine. [24][25][26] This task is especially challenging as many factors influence the protein corona formation, in particular the physicochemical properties of NPs, 27,28 such as chemical composition, 29 size, 30,31 morphology, 32 hydrophobicity, 33 chirality, 34 and surface charge. The latter has been extensively studied and there is broad consensus in the literature on the importance of electrostatic forces in protein corona formation, with positively charged NPs consistently attracting higher quantities of proteins than negatively charged ones, as reported for a range of nanomaterials such as polymeric, 35 inorganic, 36 gold, 37 or lipidbased 38 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Consequently, understanding formation of the protein corona on NPs and characterizing its composition are major challenges for suc-cessful development of nanomedicine. [24][25][26] This task is especially challenging as many factors influence the protein corona formation, in particular the physicochemical properties of NPs, 27,28 such as chemical composition, 29 size, 30,31 morphology, 32 hydrophobicity, 33 chirality, 34 and surface charge. The latter has been extensively studied and there is broad consensus in the literature on the importance of electrostatic forces in protein corona formation, with positively charged NPs consistently attracting higher quantities of proteins than negatively charged ones, as reported for a range of nanomaterials such as polymeric, 35 inorganic, 36 gold, 37 or lipidbased 38 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…BC is rapidly emerging as a critical diagnostic and therapeutic tool in nanomedicine as it mediates the interaction between living systems and nanomaterials. [ 27 ] To provide the scientific community with robust and reproducible results, efforts are aimed at standardizing experimental protocols. In this study, we demonstrate that when two independent operators execute the same experimental protocol in different laboratories highly reproducible results are obtained that are not affected by the use of automatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…This was a surprising result, because it is not immediately obvious why apolipoproteins would have significant affinity for synthetic moieties such as polystyrene-based NPs of varying spherical diameters and surface charges. Since the publication of this seminal work, several thorough studies have confirmed the binding of apolipoproteins to soft NPs that are commonly used in the clinic such as poly­(ethylene glycol) (PEG)-ylated liposomes (∼5 mol % PEG) that form the shells of anticancer treatments such as Doxil. Prominent apolipoproteins found on PEGylated liposomes include ApoAI, ApoAII, ApoB100, ApoCIII, and ApoE. There are variations in the amounts of these factors bound to each PEGylated liposome, but the overall postulate that apolipoproteins bind many types of NPs has been confirmed .…”
mentioning
confidence: 99%